The Influence of Security and Convenience on Byond By BSI User Loyalty with Satisfaction as a Mediating Variable - Lailatul Masrifah; Nurma Fitrianna (Falahiya Journal of Islamic Banking and Finance, 2026)
Introduction: This study examines the effects of security and ease of use on user loyalty toward the BYOND by BSI application, with customer satisfaction as a mediating variable. The study aims to analyze both the direct and indirect effects of security and ease of use on user loyalty. Research Methods: A quantitative approach was employed involving 100 active BYOND by BSI users at BSI KCP Ponorogo. Data were collected through questionnaires using purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The results show that security, ease of use, and customer satisfaction have positive and significant effects on user loyalty. Security and ease of use also positively and significantly influence customer satisfaction. Furthermore, customer satisfaction significantly mediates the effects of security and ease of use on user loyalty. Conclusion: Security and ease of use are important factors in enhancing user loyalty, both directly and through customer satisfaction. These findings suggest that improving system security and application usability can strengthen customer satisfaction and foster long-term loyalty in digital banking services.